An Unusual Case of Spontaneous Pneumomediastinum - Bidesh Bista; Ram Hari Ghimire; Deevya Raj Mishra (Journal of Nobel Medical College, 2020)
Spontaneous pneumomediastinum is rare condition with free air in the mediastinum. There are some controversies to consider spontaneous pneumomediastinum in patients with predisposing factors like asthma, interstitial lung disease, illicit drug users and irritant inhalations. It generally occurs due to sudden increase in intrathoracic pressure causing rupture of alveoli and movement of air to the mediastinum. Here we present a case of a 20 years old male patient with few bouts of cough as precipitating factor and development of spontaneous pneumomediastinum and subcutaneous emphysema.